0
$\begingroup$

This question is a follow-up to Proof of gauge invariance of the massless Fierz-Pauli action.

One representation of the Fierz-Pauli action (up to a prefactor) is, $$ S[h] =\int dx\left\{\underbrace{\frac{1}{2}(\partial_\lambda h^{\mu\nu})(\partial^\lambda h_{\mu\nu})}_{=:A}-\underbrace{\frac{1}{2}(\partial_\lambda h)(\partial^\lambda h)}_{=:B}-\underbrace{(\partial_\lambda h^{\lambda\nu})(\partial^\mu h_{\mu\nu})}_{=:C}+\underbrace{(\partial^\nu h)(\partial^\mu h_{\mu\nu})}_{=:D}\right\}.\tag{1} $$

We now want to show that $S[h]$ is invariant under the gauge transformation, $$ h_{\mu\nu}\rightarrow h_{\mu\nu}+\delta h_{\mu\nu},\tag{2} $$ wherein $\delta h_{\mu\nu}=\partial_\mu\xi_\nu+\partial_\nu\xi_\mu$. We demand that $\xi_\mu(x_\nu)$ falls of rapidly at the respective boundaries of the action.

i) Why is it sufficient to only consider invariance of gauge transformations up to the first-order? Even if we consider the weak gravity regime $h_{\mu\nu}\ll1$, I don't see how this should lead to $\delta h_{\mu\nu}\ll 1$.

We now start to show first-order invariance by applying the gauge transformation, Eq. (2), to the terms $A, B, C, D$.

$$ \begin{align} A &\to\frac{1}{2}(\partial_\lambda h^{\mu\nu}+\partial_\lambda \delta h^{\mu\nu})(\partial^\lambda h_{\mu\nu}+\partial^\lambda\delta h_{\mu\nu})\\ &=\underbrace{\frac{1}{2}(\partial_\lambda h^{\mu\nu})(\partial^\lambda h_{\mu\nu})}_{=A}+\underbrace{(\partial_\lambda h^{\mu\nu})(\partial^\lambda\delta h_{\mu\nu})}_{=\delta A}+\mathcal{O}(\delta h_{\mu\nu}^2)\\ B &\to\frac{1}{2}(\partial_\lambda h+\partial_\lambda \delta h)(\partial^\lambda h+\partial^\lambda\delta h)\\ &=\underbrace{\frac{1}{2}(\partial_\lambda h)(\partial^\lambda h)}_{=B}+\underbrace{(\partial_\lambda h)(\partial^\lambda\delta h)}_{=:\delta B}+\mathcal{O}(\delta h_{\mu\nu}^2)\\ C &\to(\partial_\lambda h^{\lambda\nu}+\partial_\lambda\delta h^{\lambda\nu})(\partial^\mu h_{\mu\nu}+\partial^\mu\delta h_{\mu\nu})\\ &=\underbrace{(\partial_\lambda h^{\lambda\nu})(\partial^\mu h_{\mu\nu})}_{=C}+\underbrace{2(\partial_\lambda h^{\lambda\nu})(\partial^\mu\delta h_{\mu\nu})}_{=:\delta C}+\mathcal{O}(\delta h_{\mu\nu}^2)\\ D &\to (\partial^\nu h+\partial^\nu\delta h)(\partial^\mu h_{\mu\nu}+\partial^\mu\delta h_{\mu\nu})\\ &=\underbrace{(\partial^\nu h)(\partial^\mu h_{\mu\nu})}_{=D}+2\underbrace{(\partial^\nu h)(\partial^\mu \delta h_{\mu\nu})}_{=:\delta D}+\mathcal{O}(\delta h_{\mu\nu}^2) \end{align} $$ ii) Are these results correct so far? How do I show $(\partial^\nu h)(\partial^\mu \delta h_{\mu\nu})=(\partial^\nu\delta h)(\partial^\mu h_{\mu\nu})$?

Using the previous results, we find, $$ S[h+\delta h]-S[h] =\int dx\left\{\delta A-\delta B-\delta C+\delta D\right\}+\mathcal{O}(\delta h^2).\tag{3} $$ Only $\delta B$ and $\delta D$ contain $h$, therefore, both should cancel (up to a constant) and we can consider them separate, $$ \begin{align} \int dx\left\{\delta D-\delta B\right\} &=\int dx\left\{2(\partial^\nu h)(\partial^\mu\delta h_{\mu\nu})-(\partial_\lambda h)(\partial^\lambda\delta h) \right\}\\ &=\int dx(\partial^\lambda h)\left\{2(\partial^\mu\delta h_{\mu\lambda})-(\partial_\lambda\delta h) \right\}\\ &=\int dx(\partial^\lambda h)\left\{2(\partial^\mu(\partial_\mu\xi_\lambda+\partial_\lambda\xi_\mu)-\partial_\lambda(2\partial^\mu\xi_\mu) \right\}\\ &=2\int dx(\partial^\lambda h)(\partial^2\xi_\lambda).\tag{4} \end{align} $$ Next, we examine the other two terms, $$ \begin{align} \int dx\left\{\delta A-\delta C\right\} &=\int dx\left\{(\partial_\lambda h^{\mu\nu})(\partial^\lambda\delta h_{\mu\nu})-2(\partial_\lambda h^{\lambda\nu})(\partial^\mu \delta h_{\mu\nu})\right\}\\ &=\int dx\left\{-h^{\mu\nu}(\partial^2\delta h_{\mu\nu})+2h^{\lambda\nu}(\partial_\lambda\partial^\mu \delta h_{\mu\nu})\right\}\\ &=\int dxh^{\mu\nu}\left\{-\partial^2\delta h_{\mu\nu}+2\partial_\mu\partial^\lambda \delta h_{\lambda\nu}\right\}\\ &=\int dxh^{\mu\nu}\left\{-\partial^2(\partial_\mu\xi_\nu+\partial_\nu\xi_\mu)+2\partial_\mu\partial^\lambda (\partial_\lambda\xi_\nu+\partial_\nu\xi_\lambda)\right\}\\ &=\int dxh^{\mu\nu}\left\{\partial_\mu\partial^2\xi_\nu-\partial^2\partial_\nu\xi_\mu+2\partial_\mu\partial_\nu(\partial^\lambda\xi_\lambda)\right\},\tag{5} \end{align} $$ wherein we used partial integration for the second equal and index relabeling for the third equal.

Comparing Eq. (4) and Eq. (5), we see that terms don't add up to a constant or divergence. iii) Where have I made mistakes?

$\endgroup$

1 Answer 1

1
$\begingroup$

A friend from university has helped me answer the questions:

i) Our gauge transformation is a linear transformation and therefore can be considered to form a Lie group. From Lie groups we know, that it is sufficient to show invariance only up to the first-order as we can always dissect transforms "large" in magnitude (think $\delta h\gg1$) into infinitesimal steps. If someone can put this in a more rigorous language, please do so!

ii)+iii) Actually, $(\partial^\nu h)(\partial^\mu \delta h_{\mu\nu})\neq(\partial^\nu\delta h)(\partial^\mu h_{\mu\nu})$, thus, we must correct the transformation of term $D$ to, $$ D \to (\partial^\nu h+\partial^\nu\delta h)(\partial^\mu h_{\mu\nu}+\partial^\mu\delta h_{\mu\nu})\\ =\underbrace{(\partial^\nu h)(\partial^\mu h_{\mu\nu})}_{=D}+\underbrace{(\partial^\nu \delta h)(\partial^\mu h_{\mu\nu})+ (\partial^\nu h)(\partial^\mu \delta h_{\mu\nu})}_{=:\delta D}+\mathcal{O}(\delta h_{\mu\nu}^2). $$ Now, Eq. (4) reads, $$ \begin{align} \int dx\left\{\delta D-\delta B\right\} &= \int dx(\partial^\nu h)\left\{\partial^\mu\delta h_{\mu\nu}-\partial_\nu \delta h\right\}+\int dx (\partial^\nu \delta h)(\partial^\mu h_{\mu\nu})\\ &=\underbrace{-\int dx h\partial^2\left\{\partial^\nu\xi_\nu-\partial^\mu\xi_\mu\right\}}_{=0}-\int dx h_{\mu\nu}(\partial^\mu\partial^\nu\delta h). \end{align} $$ Adding up Eq. (5) and the corrected version of Eq. (4), we find that the transformed action up to first-order indeed vanishes, $$ \begin{align} \int dx\delta S &=\int dx h^{\mu\nu}\left\{\partial_\mu\partial^2\xi_\nu-\partial^2\partial_\nu\xi_\mu+\underbrace{2\partial_\mu\partial_\nu(\partial^\lambda\xi_\lambda)-2\partial_\mu\partial_\nu(\partial^\lambda\xi_\lambda)}_{=0}\right\}\\ &=\int dx h^{\mu\nu}\partial^2\partial_\mu\partial^2\xi_\nu-\int dx h^{\nu\mu}\partial^2\partial_\mu\xi_\nu\\ &=\int dx h^{\mu\nu}\partial^2\partial_\mu\partial^2\xi_\nu-\int dx h^{\mu\nu}\partial^2\partial_\mu\xi_\nu =0, \end{align} $$ where we have used in the last steps that $h^{\mu\nu}=h^{\nu\mu}$ and that we can relabel summed indices.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge you have read our privacy policy.

Not the answer you're looking for? Browse other questions tagged or ask your own question.